Hydraulics for civil engineers - Wynn, Peter (ICE textbooks, 2014)
Hydraulics for Civil Engineers provides a fundamental introduction to the area of fluid mechanics and hydraulics. This book covers all key areas of learning including such subjects as hydrostatics; hydrodynamics; turbines and pumps; flow and waves.